RANCANG BANGUN KUNCI PINTU OTOMATIS BERBASIS MIKROKONTROLER ARDUINO MENGGUNAKAN RFID DAN SIM900 SEBAGAI SISTEM KEAMANAN - Sunardi, Riko Andika; Wijaya, Sugeng Hendra; Hidayat, Imam; Noerdyah, Pramitha Soerya (Universitas Bakti Indonesia, 2024)
This research focuses on the use of Arduino in creating an automated door system. Utilizing Arduino and RFID modules, the door automation system grants access only to valid RFID cards. The SIM900 module provides real-time notifications to the door owner. The research findings demonstrate a significant improvement in door access security and convenience compared to the keypad-based approach. It is expected that this system will serve as a safer and more effective solution to enhance home security in the era of globalization and technological advancement.